Implementasi Alokasi Dana Desa Di Desa Bontoala Kab. Gowa Dalam Mewujudkan Pembangunan - Muh. Rais Mukram Latif; Ansyarif Khalid; Saida Said (Journal Economic Excellence Ibnu Sina, 2023)
The aim of this research is to find out how village fund allocation is managed in Bontoala Village. Data collection techniques in this research were observation, interviews and documentation. Results of the Implementation of Village Fund Allocation in Bontoala Village, Kab. Gowa in Realizing Development'' shows that 1) Implementation of Village Fund Allocation in Bontoala Village has been effective. 2) Contributions generated from the Village Fund Allocation have also been fulfilled with the participation of community shops, religious leaders, youth leaders and women leaders when planning the budget. .3) The factor that hinders implementation is that many people do not understand the objectives of the development built by the village government, thus hampering the progress of development in Bontoala village.